Guideline for Reliability-Based Classification of Existing Bridges - Pedersen, Claus; ICASP14; Roldsgaard, Joan Hee; O'Connor, Alan (My University, 2023)
This paper presents the newly updated Danish guideline for reliability-based classification of existing bridges published by the Danish Road Directorate in 2023. The update of the guideline reflects the commitment to consider reliability-based assessment for all bridge structures that have failed a deterministic assessment. This is very much in-line with the high focus from the society to become more sustainable. The Danish guideline for reliability-based classification of existing bridges is unique in the sense that it gives concrete guidance for practicing engineers on how to perform a reliability-based classification of an existing bridge. The newest update of the guideline is based on decades of experience of reliability-based assessment of existing bridges in Scandinavian countries. A significant contribution to the updated guideline has been to guide the users in how model uncertainties can be quantified, assessed, and modelled in a consistent way to reflect the calibration of the Danish partial safety factors. The guidance on the formulation of critical limit states and how the critical limit state and failure mechanism is related to the target safety level has also been elaborated. Furthermore, a concrete example of a generic bridge has been included to guide the users through the most common limit states (bending moment, shear with stirrups and shear without shear reinforcement) for existing concrete bridges in Denmark.
14th International Conference on Applications of Statistics and Probability in Civil Engineering(ICASP14)
PUBLISHED